Sistem Informasi Geografis Pemetaan Rumah Tangga Miskin Pada Kecamatan Panekan Berbasis Web - Kurniawan Aminuddin, Roy Arif (LPPM Universitas Merdeka Madiun, 2019)
Mapping information system in poor households in panekan service were using the services of websites which digital maps. To make it easy for the central bureau of statistics central bureau of statistics (BPS) and the community panekan sub district in providing and to obtain any information to make a statement on information on households poor in panekan sub district, bi deputy governor muliaman d this application is reasonable enough an integrated information system for. This information system to display location mapping poor households. With information system, everybody can see the mapping and information data on poor households the. In research this one is evolved a geographical information system the mapping of poor households on panekan sub district. System development in a build and fix, because they are considered quickly in the creation of a system. System that built can are expected to help bps and the community panekan. So that system that built must have the ability to form information mapping poor households accurately. For it, geographical information system mapping households poor in panekan sub distric have tested in a blackbox.